Iron status of highly active adolescents: Evidence of depleted iron stores in gymnasts - Constantini, N. W.; Eliakim, A.; Zigel, L.; Yaaron, M.; Falk, B. (International Journal of Sport Nutrition and Exercise Metabolism, 2000)
Much attention has focused on the nutrition and hematological profile of female athletes, especially gymnasts. The few studies on iron status of male adolescent athletes found a low incidence of iron deficiency. The present study investigated the iron status of male and female gymnasts (G) and compared it with athletes of other sports. Subjects were 68 elite athletes (43 M, 25 F) ages 12Ð18, of four sports: gymnasts (11 M, 12 F), swimmers (11 M, 6 F), tennis players (10 M, 4 F), and table tennis players (11 M, 3 F). All lived in the national center for gifted athletes, trained over 25 hr a week, ate in the same dining room, and shared a similar lifestyle. Mean levels of hemoglobin (Hb), red blood cell indexes, serum ferritin, serum iron, and transferrin were measured in venous blood. There was no difference in mean Rb among gymnasts (G) and nongymnasts (NG). However, Hb was less than 14 g/dL in 45% of M G vs. only 25% in NG, and less than 13 g/dL in 25% of premenarcheal F G vs. 15% in NG. Low transferrin saturation (<20%) was detected in 18% of M G and 25% of F G vs. 6% and 8% in male and female NG, respectively (p < .05). The percentage of males suffering from low ferritin level (<20 ng/ml) was twice as high in G (36%) vs. NG (19%), and about 30% in all females. In summary, iron stores were consistently lower in M G vs. NG. Adolescent athletes of both genders, G in particular, are prone to nonanemic iron deficiency, which might compromise their health and athletic performance.